MRNA-seq reveals skeletal muscle atrophy in response to handling stress in a marine teleost, the red cusk-eel (Genypterus chilensis). (December 2015) - Aedo, Jorge; Maldonado, Jonathan; Aballai, Víctor; Estrada, Juan; Bastias-Molina, Macarena; Meneses, Claudio; Gallardo-Escarate, Cristian; Silva, Herman; Molina, Alfredo; Valdés, Juan
Abstract Background Fish reared under intensive conditions are repeatedly exposed to stress, which negatively impacts growth. Although most fish follow a conserved pattern of stress response, with increased concentrations of cortisol, each species presents specificities in the cell response and stress tolerance. Therefore, culturing new species requires a detailed knowledge of these specific responses. The red cusk-eel (Genypterus chilensis ) is a new economically important marine species for the Chilean aquaculture industry. However, there is no information on the stress- and cortisol-induced mechanisms that decrease skeletal muscle growth in this teleost. Results Using Illumina RNA-seq technology, skeletal muscle sequence reads forG. chilensis were generated under control and handling stress conditions. Reads were mapped onto a reference transcriptome, resulting in thein silico identification of 785 up-regulated and 167 down-regulated transcripts. Gene ontology enrichment analysis revealed a significant up-regulation of catabolic genes associated with skeletal muscle atrophy. These results were validated by RT-qPCR analysis for ten candidates genes involved in ubiquitin-mediated proteolysis, autophagy and skeletal muscle growth. Additionally, using a primary culture of fish skeletal muscle cells, the effect of cortisol was evaluated in relation to red cusk-eel skeletal muscle atrophy. Conclusions The present data demonstrated that handling stress promotes skeletal muscle atrophy in the marine teleostG. chilensis through the expression of components of the ubiquitin-proteasome and autophagy-lysosome systems. Furthermore, cortisol was a powerful inductor of skeletal muscle atrophy in fish myotubes. This study is an important step towards understanding the atrophy system in non-model teleost species and provides novel insights on the cellular and molecular mechanisms that control skeletal muscle growth in early vertebrates.